2018
DOI: 10.1016/j.jbmt.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A critical overview of the current myofascial pain literature – April 2018

Abstract: Twenty-four basic and clinical studies and case reports are included in this quarterly review of the myofascial pain literature. The majority of publications focus on invasive techniques, especially dry needling. We hope, that this not suggest that clinicians and researchers are slowly moving away from manual trigger point (TrP) approaches. While some physiotherapists have bought into the notion that hands-on approaches are a thing of the past, since "pain is in the brain" and "the issues are not in the tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…Os pontos gatilhos, quando estimulados, ocasionam dor referida, causada pelo enclausuramento de terminações nervosas. (FRICTON et al, 2016;SIMONS 2008;DOMMERHOLT et al,2016). A pressão sobre o ponto potencializa o padrão de referência que pode ser causada por forte input nóxico aferente, com envolvimento de padrões dermatômicos, miotômicos e esclerotômicos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os pontos gatilhos, quando estimulados, ocasionam dor referida, causada pelo enclausuramento de terminações nervosas. (FRICTON et al, 2016;SIMONS 2008;DOMMERHOLT et al,2016). A pressão sobre o ponto potencializa o padrão de referência que pode ser causada por forte input nóxico aferente, com envolvimento de padrões dermatômicos, miotômicos e esclerotômicos.…”
Section: Discussionunclassified
“…Os pontos gatilhos ativos são normalmente identificados nos músculos posturais da região cervical, cintura escapular e pélvica, escaleno, esternocleidomastoideo, elevador da escápula, quadrado lombar e musculatura mastigatória (FRICTON et al, 2016;SIMONS 2008;DOMMERHOLT et al, 2016). O padrão de palpação do músculo trapézio da região cervical para localização da banda tensa, com finalidade de encontrar o ponto gatilho mais sensível, foi definido juntamente com o intervalo de tempo de zero, 5 e 10 minutos considerando a variação de velocidade de disparo de inputs nóxico sensitivos, através de estudo piloto (MACIEL et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dry needling (DN) is used to treat musculoskeletal injuries, pain, and muscle tension reduction [29][30][31]. Most of the current literature has shown the effectiveness of DN on latent trigger points [32][33][34], but there has also been success in its use to increase range of motion (ROM) after a muscle strain [35] and after an ACL reconstruction [30]. Myofascial pain is a common form of pain that arises from muscles or related fascia and is usually associated with myofascial trigger points (MTrP) and musculoskeletal injuries [33].…”
Section: Hivamat and Theragun Are Two Varieties Of Handheld Vibrationmentioning
confidence: 99%
“…Myofascial pain is a common form of pain that arises from muscles or related fascia and is usually associated with myofascial trigger points (MTrP) and musculoskeletal injuries [33]. An MTrP is a highly localized, hyperirritable spot in a palpable, taut band of skeletal muscle fiber [34,36]. Research has found that MTrPs are reported as a primary source of pain in a majority of musculoskeletal pain patients, as well as in many other types of patients from chronic widespread pain to headaches [37][38][39][40].…”
Section: Hivamat and Theragun Are Two Varieties Of Handheld Vibrationmentioning
confidence: 99%